(untitled) (Research, Society and Development, 2020)
Tooth brushing is considered an indispensable method for maintaining oral health. Contudo, many studies prove that dental brooms can be favorable environments for microorganisms. These microorganisms can proliferate, becoming a source for auto-infections and cross-infections, being necessary disinfection procedures to avoid health damage. In view of this, the objective of the study was to review the disinfecting agents and disinfection methods of dental brooms present in the literature. A wide search was made through the PubMed / MEDLINE, LILACS, CAPES Periódicos Portal, Scientific Electronic Library Online (SCIELO) e Biblioteca Virtual de Saúde (BVS) databases, covering the period two last 20 years, in addition to a not Google Schoolar. The search was carried out in the months of July to August 2020 and the descriptors used include a combination of therms: “toothbrushing”, “disinfectants” and “biocides” and theirs derivatives, as well as free therms such as “toothbrush” and “cleaning” adapting for each databases searched. First of all, it was made a selection through titles and abstracts, being 16 articles included in study. From the complete reading of studies, we find several disinfectant agents available, including: chlorhexidine digluconate, ultraviolet rays, sodium hypochlorite, acetic acid, triclosan, alcoholic solution, cetylperidinium chlorette, hydrogen peroxide, iron oxide essenciais. UV rays, digluconate-based mouthwashes with chlorhexidine (spray) are the most efficient to reduce the bacterial and fungal load of toothbrushing dentais. In the meantime, there are still some answers that will be answered.